KARAKTERISTIK FISIKOKIMIA DAN SENSORIS SELAI BUAH SIWALAN DENGAN PENAMBAHAN EKSTRAK KULIT BUAH NAGA MERAH - Mubarak, Muhammad Zainun Syauqil; Mulyadi, Mochtar Nova (Jurnal Pangan dan Gizi, 2024)
Red dragon fruit contains bioactive compounds that are beneficial for body health, including antioxidants such as ascorbic acid, beta-carotene, and anthocyanins, as well as dietary fiber in the form of pectin. This study aims to assess the impact of adding red dragon fruit peel extract on the physicochemical and organoleptic quality of siwalan fruit jam. Jam was made with variations in the addition of red dragon fruit peel extract of 0 ml (control), 100 ml, 120 ml, and 140 ml. The parameters tested included water content, protein content, and organoleptic responses including taste, aroma, color, and texture. The findings in this study showed that the addition of red dragon fruit peel extract significantly reduced the water content of the jam, from 37.67% in the control to 27.24% in the treatment with 140 ml of extract, which can increase the resistance of the jam to microbes. The addition of extract also had a positive impact on the attributes of taste, color, and texture. The highest taste and texture assessment scores were achieved in the treatment with 140 ml of extract, indicating better panelist preference. Although the protein content was not significantly affected by the addition of the extract, the addition of red dragon fruit peel extract improved the stability and elasticity of the jam. Thus, red dragon fruit peel extract can be used to improve the quality of siwalan fruit jam in terms of physicochemical and sensory.